2006
DOI: 10.1093/gerona/61.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Strength, But Not Muscle Mass, Is Associated With Mortality in the Health, Aging and Body Composition Study Cohort

Abstract: Low muscle mass did not explain the strong association of strength with mortality, demonstrating that muscle strength as a marker of muscle quality is more important than quantity in estimating mortality risk. Grip strength provided risk estimates similar to those of quadriceps strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
1,005
8
41

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,409 publications
(1,092 citation statements)
references
References 27 publications
38
1,005
8
41
Order By: Relevance
“…These cross-sectional results could suggest that poor muscle strength should be preferred above low muscle mass to assess sarcopenia. This is supported by the findings of other epidemiological studies showing that muscle strength measures in older persons are more strongly associated with (change in) functional limitations and disability (15)(16)(17)(18) and mortality (19)(20) compared to muscle mass measures.…”
Section: Definitions Of Sarcopeniasupporting
confidence: 83%
“…These cross-sectional results could suggest that poor muscle strength should be preferred above low muscle mass to assess sarcopenia. This is supported by the findings of other epidemiological studies showing that muscle strength measures in older persons are more strongly associated with (change in) functional limitations and disability (15)(16)(17)(18) and mortality (19)(20) compared to muscle mass measures.…”
Section: Definitions Of Sarcopeniasupporting
confidence: 83%
“…Lower-limb muscle strength has been shown to be a good predictor of incident mobility limitations (40), hospitalization (41) and death (42) in older adults. In this regard, previous studies linking diabetes with reduced walking speed (39,(43)(44)(45) have attributed this association to the accelerated loss of skeletal muscle strength that is commonly seen in older adults with this metabolic disease (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that diminished bioenergetic reserve (Schrack et al ., 2013) and/or impaired bioenergetic synthetic capacity is in part responsible for slower walking speeds in older persons. This hypothesis is consistent with the progressive decline in muscle mass and strength (with the decline in strength outpacing that of muscle mass) (Goodpaster et al ., 2006; Newman et al ., 2006) often observed in older persons and attributed in part to higher prevalence of chronic diseases (McDermott et al ., 2004) and lower physical activity in older compared with younger persons (Cesari et al ., 2009). …”
Section: Introductionmentioning
confidence: 99%